AUS-UAV HILS Setup of Dynamic Flight Path Planning - Hasan, Mohammed Mahedi (2006)
A Master of Science Thesis in Mechatronics Submitted by Mohammed Mahedi Hasan Entitled, "AUS-UAV HILS Setup of Dynamic Flight Path Planning," August 2006. Thesis Advisor is Dr. Mohammed Ameen Al-Jarrah. Available are both Soft and Hard Copies of the Thesis.